Constructing Ideology through Modality in Newspaper Editorials on Security Challenges in Nigeria - Alfred , Bukola (Linguistik Online, 2021)
This paper explores Nigerian media’s deployment of modality on editorials on security challenges in Nigeria. The study examines how such impress on the ideological position of the media on the security issues in Nigeria. The study relates to how well Nigerian newspaper organisations attempted to reveal or mask security cases across different regions of the country through modal options. The editorials were sourced from The Punch and The Guardian (South-Western region), Vanguard and The Sun (East) and Leadership and Daily Trust (Northern Region) between 2014 and 2016. The frequencies and percentages of occurrences of these modality markers were examined and their implications were interpreted to reflect the attitudes and dispositions of the newspapers to security issues. Our findings show that the six newspapers expressed unbiased concerns over the Boko-Haram Insurgency whether or not the newspaper is situated in the northern region. However, the fact that certain security issues emanated from particular regions also prompted the kinds of modal markers employed by specific newspapers representing such regions. The Sun’s choices of modal indirectly expressed support for their plights and protests of the pro-Biafra agitators. The Punch’s choices of modal verbs portrayed President Buhari as sharing some ethnic affinity with herders.